The functions of adequate communication in the neonatal care unit: A systematic review and meta-synthesis of qualitative research. Issue 7 (July 2021) - Wreesmann, Willem-jan W.; Lorié, Esther S.; van Veenendaal, Nicole R.; van Kempen, Anne A.M.W.; Ket, Johannes C.F.; Labrie, Nanon H.M.
Highlights: Parent-provider interaction plays a significant role in Family-Integrated Care. Yet, understanding of the functions of (adequate) NICU communication was lacking. Meta-synthesis of 43 qualitative studies revealed the NICU Communication Framework. There are four distinct functions of parent-provider communication in neonatal care. Five factors determine parent-provider communication adequacy (mnemonic: TAILORED). Abstract: Objective: To assess the main functions of parent-provider communication in the neonatal (intensive) care unit (NICU) and determine what adequate communication entails according to both parents and health professionals. Methods: A systematic review and meta-synthesis of qualitative research. PubMed, Ebsco/PsycINFO, Wiley/Cochrane Library, Ebsco/CINAHL, Clarivate Analytics/Web of Science Core Collection, and Elsevier/Scopus were searched in October-November 2019 for records on interpersonal communication between parents and providers in neonatal care. Title/abstract screening and full-text analysis were conducted by multiple, independent coders. Data from included articles were analyzed using deductive and inductive thematic analysis. Results: 43 records were included. Thematic analysis of data resulted in the development of the NICU Communication Framework, including four functions of communication (1. building/maintaining relationships, 2. exchanging information, 3. (sharing) decision-making, 4. enabling parent self-management) and five factors that contribute to adequate communication across these functions ( topic, aims, location, route, design) and, thereby, to tailored parent-provider communication. Conclusion: The NICU Communication Framework fits with the goals of Family Integrated Care to encourage parent participation in infants' care. This framework forms a first step towards the conceptualization of (adequate) communication in NICU settings. Practice implications: Findings can be used to improve NICU communication in practice, in particular through the mnemonic TAILORED.